Rethinking Medieval Ireland and Beyond
1 online resource
Keywords: This volume brings together scholarship from many disciplines, including history, heritage studies, archaeology, geography, and political science to provide a nuanced view of life in medieval Ireland and after. Primarily contributing to the fields of settlement and landscape studies, each essay considers the influence of Terence B. Barry of Trinity College Dublin within Ireland and internationally. Barry’s long career changed the direction of castle studies and brought the archaeology of medieval Ireland to wider knowledge. These essays, authored by an international team of fifteen scholars, develop many of his original research questions to provide timely and insightful reappraisals of material culture and the built and natural environments. Contributors (in order of appearance) are Robin Glasscock, Kieran O’Conor, Thomas Finan, James G. Schryver, Oliver Creighton, Robert Higham, Mary A. Valante, Margaret Murphy, John Soderberg, Conleth Manning, Victoria McAlister, Jennifer L. Immich, Calder Walton, Christiaan Corlett, Stephen H. Harrison, and Raghnall Ó Floinn.